Stosunek instytucji państwowych i kościelnych do dwudziestowiecznych polskich wizjonerek w świetle zgromadzonych danych zastanych. Wyniki badań (Przegląd Religioznawczy – The Religious Studies Review, 2022)
The objective of the article is to present the results of research funded by the National Science Centre in 2018–2019, aimed at finding and exploring existing data concerning the late Polish visionaries Katarzyna Szymon and Jadwiga Bartel. The former lived between 1907 and 1986 in Silesia, while the other lived in the Kuyavia region between 1911 and 1993. During investigations conducted in 2019, 287 archival units spanning approximately 20,670 pages were consulted in 9 secular and church archives to find material which could provide new information about those visionaries. The archival research yielded previously unknown details about their lives and people who supported them, though the particulars were mainly related to secular matters or those on the juncture of the secular and religious domains.